PENINGKATAN KEMAMPUAN PENGENALAN BENTUK GEOMETRI MELALUI MEDIA BANNER: STUDI DI TK AISYIYAH BUSTANUL ATHFAL 81 BEKASI - Nurjanah, Siti; Masbukhin, Faizal Akhmad Adi (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2024)
This research aims to enhance the ability of early childhood to recognize geometric shapes through the use of banner media at TK Aisyiyah Bustanul Athfal 81, Bekasi City. The identified problem is the lack of children's ability to recognize and categorize geometric shapes. The method employed is the application of the problem-based learning (PBL) model and the use of creative and innovative banner media in geometric games, such as jumping on geometric-shaped carpets, arranging similar geometric shapes, and creating geometric shapes from playdough. The research results show a significant improvement in the ability to recognize geometric shapes in children. The learning success rate reaches 93%, indicating the effectiveness of this approach. This study concludes that geometric games with banner media at TK Aisyiyah Bustanul Athfal 81, Bekasi City are effective in enhancing the ability of early childhood to recognize geometric shapes. This approach not only introduces geometric shapes but also stimulates children's creativity and makes the learning process more engaging and beneficial. The implication of this research underscores the importance of applying creative and innovative teaching methods to enhance children's ability to understand mathematical concepts visually and interactively.